Peran Modal Sosial Masyarakat dalam Pengelolaan Potensi Alam Sebagai Strategi Bertahan Hidup di Dusung Limang, Kecamatan Kelapa, Kabupaten Bangka Barat - Nopa Laura; Rani Dian Sari; Irfandi Setiawan; Herdiyanti Herdiyanti (Society, 2018)
This research focuses on one remote area or often referred to as hamlet. Limang Hamlet is one of the focuses of this research. This study uses descriptive qualitative research methods, with data collection techniques using pusposive sampling. The results of the research found in the field Social capital has become an important role in people's lives, especially rural communities. Therefore the community of Limang hamlet built the structure of the community's economy through recording and managing natural potential as a survival strategy in Limang Hamlet, Kelapa District, West Bangka Regency. This condition is supported by utilizing existing social capital in the Limang Hamlet community aimed at improving economic conditions to become more prosperous. The use of social capital carried out by the community of Limang Hamlet is done by bonding, bridging and linking. Social capital which is the reference for analyzing this research uses the theory of Woolcock. These three types of social capital are applied by the people of Limang Hamlet in developing their economy. The expansion of networks both internally and externally has been carried out effectively. Movements made made the people of Limang Hamlet known in many circles. Of course, with the use of natural potential owned by the community, helping people become more developed and productive.